1987
DOI: 10.1093/nar/15.3.1311
|View full text |Cite
|
Sign up to set email alerts
|

Electroporation for the efficient transfection of mammalian cells with DNA

Abstract: A simple and reproducible procedure for the introduction of DNA into mammalian cells by electroporation is described. The parameters involving the cells, the DNA, and the electric field are investigated. The procedure has been applied to a broad range of animal cells. It is capable of transforming more than 1% of the viable cells to the stable expression of a selectable marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
365
1
4

Year Published

1988
1988
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 836 publications
(378 citation statements)
references
References 27 publications
8
365
1
4
Order By: Relevance
“…These cells were transfected by electroporation using a Biorad Gene Pulser (Chu et al, 1987). Cells to be stimulated with 10 ng/ml epidermal growth factor (EGF) or 50 nM phorbol 12-myristate 13-acetate (PMA) were ®rst grown overnight in low serum-containing medium (DMEM with 0.5% calf serum).…”
Section: Cell Culturementioning
confidence: 99%
“…These cells were transfected by electroporation using a Biorad Gene Pulser (Chu et al, 1987). Cells to be stimulated with 10 ng/ml epidermal growth factor (EGF) or 50 nM phorbol 12-myristate 13-acetate (PMA) were ®rst grown overnight in low serum-containing medium (DMEM with 0.5% calf serum).…”
Section: Cell Culturementioning
confidence: 99%
“…9 To overcome these problems, non-viral methods have been developed, [10][11][12][13][14] and one such method is electrotransfection (or electro-gene transfer). [15][16][17][18][19][20][21] Comparing with viralbased methods, electrotransfection does not require packing of genes into vectors and is less immunogenic. The technique relies on delivery of a sequence of electric pulses to target cells or tissues placed between electrodes, which leads to the entry of cell-impermeable molecules, including plasmid DNA (pDNA).…”
Section: Introductionmentioning
confidence: 99%
“…The lower transfection efficiencies reported by other authors using various electroinjection protocols (Potter et al, 1984;Toneguzzo et al, 1986) may in part be attributed to Iack of attention to one or more of the aforementioned considerations. Only Chu et al (1987) have reported stable transfection rates as high as 1%, but this was achieved in a variety of adherent monolayer cells by applying very long duration pulses (7 ms) of relatively low voltage and using DNA concentrations of 20 JLg/ml with 500 JLg/ml carrier DNA. Such long pulse durations would be expected to result in irreversible membrane breakdown and to result in the death of many otherwise viable cells.…”
Section: Discussionmentioning
confidence: 99%